Aportes a la iconografía de Daniel Carrión García - Álvarez Carrasco, Ricardo Iván (2012)
This article provides innovative and unpublished contributions on Daniel Carrion-Garcia’s iconography (1857-1885) -hero and martyr of Peruvian medicine- based on material evidence showing that one of the two portraits attributed to him corresponds to photographer Rafael Castillo, who worked in Lima between 1860 and 1890.